ELEKTR ENERGIYASINI UZATISH TARMOQLARIDAGI XARAJATLARNI MINIMALLASHTIRISHNI MATEMATIK MODELLASHTIRISH - Orinbaev, A.B.; Axunbetova, Z.N. (SCIENCE and SOCIETY, 2024)
The article proposes a new mathematical model that allows minimizing costs associated with electrical losses during the distribution and transmission of electrical energy. Also, using a mathematical model, numerical experiments were carried out and optimal solutions were obtained.
Keywords: electric power; distribution; optimization; linear programming